Magnetic phase transitions in cobalt chromite nanoparticles - Rath C.; Mohanty P. (My University, 2025)
Cobalt chromite (CoCr 2O 4), an insulating normal spinel compound, is a potential multiferroic material. We report that pure, nanosize CoCr 2O 4 particles are synthesized through a conventional coprecipiation technique by controlling the pH of the precipitation. Both single-crystal and polycrystalline samples develop long-range ferrimagnetic order below the Curie temperature, T c (97 K), and a sharp phase transition at T s ∼ 31 K, attributed to the onset of long-range spiral magnetic order. However, we observed a transition from paramagnetic to superparamagnetic phase at T c. Further lowering the temperature below T c (97 K), the superparamagnetic phase transforms to ferrimagnetic phase at blocking temperature, T b, which is found to be between 50 and 60 K. This intermediate superparamagnetic phase in between paramagnetic and long-range ferrimagnetic phases is attributed to a nanosize effect. © Springer Science+Business Media, LLC 2010.